GEOSPATIAL ASSESSMENT BASED ON FERTILITY AND MORTALITY DIFFERENTIAL INDICES OF NATURAL SELECTION IN NORTH-WEST AND EASTERN HIMALAYAN POPULATIONS. Issue 6 (20th December 2016) - Sharma, Krishan
Summary: There is contradictory evidence of having fewer live births and higher embryonic mortality among high-altitude populations than their counterparts at lower altitude. This study explores the geospatial differences in selection intensities among human populations living in different ecological settings. Reproductive data from post-menopausal women were collected from 75 women from near Shimla, Himachal Pradesh, at an altitude of 2150 m above sea level and 100 women from Jind, Haryana, at an altitude of 227 m. Secondary data were taken from 85 women from the Kinnaur district of Himachal Pradesh at an average altitude of 3420 m. A comparison of the study data was made with similar data from different populations living in the western and eastern Himalayas. The total selection intensity index based on Johnston and Kensinger's index was highest in Shimla and lowest in Kinnaur. The fertility selection component was highest in Shimla and lowest in Kinnaur. The prenatal mortality contribution to the total selection was highest in Shimla (30.76%) and lowest in Kinnaur (2.14%), while the contributions of normalized postnatal mortality were 16.39% and 57.80% in Shimla and Kinnaur, respectively. The fertility component of selection was higher than the mortality component in Shimla, while in the other two places the reverse was observed. Hypoxic conditions at high altitude seem to have little effect on the fertility and embryonic mortality rates of indigenous people. The geospatial differences in the selection intensities may be due to differences in ethnic, behavioural ecology, environmental, cultural and socioeconomic factors.